Pengaruh Kepuasan Kerja terhadap Kualitas Pelayanan, Kepuasan Pelanggan dan Loyalitas Pelanggan pada Perguruan Tinggi Swasta (PTS) di Jawa Timur - Sukotjo, Hendri (Universitas Brawijaya, Indonesia, 2011)
High employee job satisfaction can provide the best service quality which in turn to create customer satisfaction and loyalty. The purpose of this study is to determine the effect of job satisfaction on service quality, customer satisfaction and customer loyalty at Private University in East Java. This study employed causal research, unit analysis are several Private University, with consisting respondent are service providers (managers, lecturer and administration staff) also student (as service costumer). Descriptive analysis techniques and SEM (structural equation model) used. The results stated that: 1. Job satisfaction is directly able to improve service quality and customer satisfaction. When connected indirectly with customer satisfaction through an intervening variable service quality, the results of its total effect becomes increasingly large. 2. Job satisfaction is directly has not been able yet to increase customer loyalty, the result is negative and significant impact. However, while connected indirectly through intervening variables such as service quality and customer satisfaction, the results turned positive total effect.